Inconsistency detection and resolution for context-aware middleware support. - Xu, Chang
Context-awareness is a key feature of pervasive computing whose environments keep evolving. The support of context-awareness requires comprehensive management including detection and resolution of context inconsistency, which occurs naturally in pervasive computing. In this paper we present a framework for realizing dynamic context consistency management. The framework supports inconsistency detection based on a semantic matching and inconsistency triggering model, and inconsistency resolution with proactive actions to context sources. We further present an implementation based on the Cabot middleware. The feasibility of the framework and its performance are evaluated through a case study and a simulated experiment, respectively.
Keywords: Software; Software engineering; Requirements / Specifications; Methodologies (e.g., object-oriented, structured).; Algorithms; Design; Management; Performance; Context consistency management; Context modeling; Pervasive computing; Proactive repairing; Semantic matching